O ensino das disciplinas ligadas ?? ??rea de finan??as nos cursos superiores de administra????o no munic??pio de S??o Paulo - Roman, Emilson (2006)
This study aims to analyze programmatic content of subjects related to Finances area in Business Administration Courses in S??o Paulo City. The content analyzed showed us a set of subject program components, in which we can lay stress on: subject title, quantity of hours, courses periodicity, summaries, objectives, teaching strategies, evaluation methods, and, finally, basic and complementary bibliography used on course. The research, based on necessity of providing a better comprehension of educational context , resulted on Brazilian Higher Teaching evolution study, laying stress on Business Administration. The research core was elaborated by analyzing 32 institutions teaching programs located in S??o Paulo City. On this research, we could observe the omission of important items: lack of standardization, problems with programmatic content, excess of content items, problems on summaries elaboration, and, lack of correlation between quantity of hours attributed to a subject and the results on "Prov??o" tests. Therefore, this study can be useful as an instrument for educators and courses coordinators reflection, in order to go in direction to a higher course that is appropriated to actual educational legislation demands, as well as to society aspirations.